2014
DOI: 10.5500/wjt.v4.i3.183
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune diabetes recurrence should be routinely monitored after pancreas transplantation

Abstract: Autoimmune type 1 diabetes recurrence in pancreas grafts was first described 30 years ago, but it is not yet completely understood. In fact, the number of transplants affected and possibly lost due to this disease may be falsely low. There may be insufficient awareness to this entity by clinicians, leading to underdiagnosis. Some authors estimate that half of the immunological losses in pancreas transplantation are due to autoimmunity. Pancreas biopsy is the gold standard for the definitive diagnosis. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 29 publications
1
9
0
8
Order By: Relevance
“…In our series, before pancreas transplantation, 15.8% and 7.3% of patients presented increased GADA and IA-2A values, respectively. These data are similar to those described by Martins et al [13], who reported that 21.5% of patients were positive for GADA, 10.4% were ICA-positive, and 3% were IAA-positive before SPK transplantation, GADA being the most frequently positive autoimmune marker [13]. However, none of the patients who were positive for GADA and IA-2A before the transplant had a subsequent T1DM recurrence.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…In our series, before pancreas transplantation, 15.8% and 7.3% of patients presented increased GADA and IA-2A values, respectively. These data are similar to those described by Martins et al [13], who reported that 21.5% of patients were positive for GADA, 10.4% were ICA-positive, and 3% were IAA-positive before SPK transplantation, GADA being the most frequently positive autoimmune marker [13]. However, none of the patients who were positive for GADA and IA-2A before the transplant had a subsequent T1DM recurrence.…”
Section: Discussionsupporting
confidence: 89%
“…However, none of the patients who were positive for GADA and IA-2A before the transplant had a subsequent T1DM recurrence. Hence, pretransplant autoantibody positivity does not seem to predict future pancreas graft endocrine function or diabetes recurrence [13,22].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations